Adaptive AC autoreclosing scheme in MMC‐based hybrid AC/DC transmission. Issue 19 (24th September 2019) - Wang, Ting; Song, Guobing; Hussain, Kazmi Sayed Tassawar
Abstract : Modular multilevel converter (MMC) is widely used in hybrid AC/DC power transmission system. Strong control capability of MMC provides a new way of the adaptive autoreclosing scheme in such systems to enhance the power supply reliability and system stability. A novel fault identification method is proposed in this study. It is based on characteristic signal injection utilising the control strategy of MMC and line coupling features. A characteristic signal from MMC can be injected to healthy lines which in turn induce characteristic signal to the faulty phase/line. Induced signals have different performances under normal or fault conditions. The proposed method is independent of electrical characteristics of recovery voltage and secondary arc, and multiple independent injections could be implemented. Finally, the adaptive autoreclosing scheme based on injection method is proposed. Simulation studies are carried out under the single line to ground and symmetrical faults, which strongly verify the effectiveness of the proposed scheme.